A SHIFT OF THE ENDOTHELIAL DYSFUNCTION MARKERS IN PATIENTS WITH HIV-INFECTION/AIDS UNDER HAART - Moskaliuk, V.D.; Sorokhan, V.D.; Melenko, S.R.; Balaniuk, I.V. (Інфекційні хвороби, 2013)
On the basis of inspection 127 patients with HIV-infection/AIDS it is set that at this pathology substantially grows concentration of thrombomodulin, and von Willebrand factor, which specifies on HIV-induced of vascular wall defeat. As far as progress of immunogenicity the concentration of all of the noted indexes grows for certain. 3-monthly symptomatic therapy does not influence on the state of endothelia.